СONTINUITY OF HUMAN PROBLEMS WITH RELIGIOUS TEXTS IN THE WORK OF ABU NASR AL-FARABI «VIEWS OF THE INHABITANTS OF THE MERCIFUL CITY» - Ы.М. Пaлтөре (Journal of Oriental Studies, 2019)
This article describes in detail that the spirit, soul, body, heart, and common human problems are associated with religious texts in the treatise of Al-Farabi named after “Mabadi ara ahl al-madina al-fadila ua mudadatiha” (views of the inhabitants of the merciful city). It also concludes that Abu Nassyr al-Farabi composed two things, namely, the residents of the “merciful city and the ignorant city” and gave a com- parative explanation of them - based on the method of the Koran. In the works of Abu Nasr al-Farabi, the “views of the inhabitants of a merciful city” regulate the conditions of life in society; the relations between society, a subordinate and the ruler are explained in the light of religious ideas. Key words: al-Farabi, merciful city, Koran, human issues, religious texts.